2016
DOI: 10.1007/s40091-016-0122-0
|View full text |Cite
|
Sign up to set email alerts
|

The influence of coupled horizontal–vertical ground excitations on the collapse margins of modern RC-MRFs

Abstract: With the increasing interest in vertical ground motions, the focus of this study is to investigate the effect of concurrent horizontal-vertical excitations on the seismic response and collapse fragilities of RC buildings designed according to modern seismic codes and located near active faults. It must be stressed that only mid-to high-rise buildings are of significant concern in the context of this research. The considered structures are categorized as intermediate and special RC-MRFs and have been remodeled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Similarly, the seismic fragility of high-rise RC frame-core wall buildings has been scrutinized through the IDA procedure, yet the risk of collapse has been neglected (Taslimi et al, 2021). Calculating the collapse margins and mean annual frequency of collapse of RC-MRFs under multi-component near-field records revealed the fact that ignoring the vertical component in analysis leads to the under-estimation of collapse risk because of its influence on the local and global performance of the buildings (Farsangi and Tasnimi, 2016). Despite this attempt to highlight the effects of vertical earthquake waves on the collapse risk, this study is limited only to RC frames, so the performance of shear or core walls remained obscure.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the seismic fragility of high-rise RC frame-core wall buildings has been scrutinized through the IDA procedure, yet the risk of collapse has been neglected (Taslimi et al, 2021). Calculating the collapse margins and mean annual frequency of collapse of RC-MRFs under multi-component near-field records revealed the fact that ignoring the vertical component in analysis leads to the under-estimation of collapse risk because of its influence on the local and global performance of the buildings (Farsangi and Tasnimi, 2016). Despite this attempt to highlight the effects of vertical earthquake waves on the collapse risk, this study is limited only to RC frames, so the performance of shear or core walls remained obscure.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, with the increasing interest in the effect of vertical ground excitations, researchers have begun to pay more attention to civil structures subjected to such effects. Farsangi and Tasnimi evaluated the coupled effect of horizontal–vertical ground motions on the collapse margins of modern reinforced concrete‐moment resisting frames. The result indicated that vertical ground motion has a significant impact on both local and global structural response and cannot be neglected.…”
Section: Introductionmentioning
confidence: 99%
“…Further, seismic vulnerability assessment of the structural models is modelled with and without infill and analyzed using CSM, and IDA approaches [13,14]. Seismic vulnerability of a structure is defined as proneness to damage under seismic excitation for a given intensity measure [1,[15][16][17][18][19][20]. It is expressed as a relationship between intensity measure and damage measure.…”
Section: Introductionmentioning
confidence: 99%